MOISTURE METER CORRECTION FACTORS FOR FOUR BRAZILIAN WOOD SPECIES. - GILLIS, CHRISTOPHER M. ; STEPHENS, W. COLE ; PERALTA, PERRY N.
THE SPECIES CORRECTION FACTORS DURING MOISTRE CONTENT MEASUREMENT OF JATOBA (HYMENAEA COURBARIL), MANDIOQUIERA (QUALEA PARAENSIS), QUARUBARANA (ERISMA UNCINATUM), AND QUARUBATINGA...
Sala de Colecciones abiertas
Inglés
R2290
FORE
Keywords: PRODUCTOS FORESTALES; ESPECIES FORESTAL; Artículos de revista